Proceedings of the 5th Universitas Ahmad Dahlan Public Health Conference (UPHEC 2019) 2020
DOI: 10.2991/ahsr.k.200311.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age, Work Period, and Work Duration on Musculoskeletal Disorders in Laundry Workers

Abstract: Ergonomics is one of the factors that can provide comfort and safety for workers who are then able to increase company productivity. Neglecting ergonomic factors can cause the risk of Musculoskeletal Disorders (MsDs) that can damage tissues such as muscles, nerves, tendons, joints and cartilage. Based on the prevalence of musculoskeletal disease in Indonesia, obtained data show as much as 11.9% are fishermen, farmers while 31.2% are labourers, including laundry workers. This study aimed to investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The Kruskal-Wallis test analysis found no statistically significant link between age, work time, or labour length and MSDs in laundry staff. As a consequence, the study concludes that these features have no effect on the incidence of musculoskeletal issues among laundry workers [10].…”
Section: Literature Reviewmentioning
confidence: 81%
“…The Kruskal-Wallis test analysis found no statistically significant link between age, work time, or labour length and MSDs in laundry staff. As a consequence, the study concludes that these features have no effect on the incidence of musculoskeletal issues among laundry workers [10].…”
Section: Literature Reviewmentioning
confidence: 81%
“…Ali's research found that there was no significant relationship between the duration of using a laptop and the health complaints that were felt due to the use of a laptop. [13][14][15] In addition, Tjahayuningtyas's research (2019) showed work period has a relationship with the musculoskeletal disorder (p 0.019). 16 The maximum duration of each laptop use is two hours.…”
Section: Discussionmentioning
confidence: 99%